SAT0346 Systemic sclerosis's early stages and its significance in daily practice. (15th June 2017) - Abreu, JP; Almeida, I; Marinho, A; Vasconcelos, C
Abstract : Background: Systemic Sclerosis (SSc) is an autoimmune disease, characterized by skin and internal organs fibrosis. Its clinical manifestations are heterogeneous, hence, the definitive diagnosis of SSc rely on scores, such as American College of Rheumatology (ACR) for SSc. Leroy and Medsger, proposed the potential criteria for the classification of early stages of SSc, due to the insufficient sensitivity previous methods. Lately EUSTAR proposed the concept of Very Early SSc, defined by the presence of 3 red flag – RF, Puffy Fingers and ANA; if 2 of these are present, capilaroscopy and specific antibody must be accessed; if one of the last positive, further search for Systemic involvement must be taken in account. Objectives: We propose to: analyse a group of patients that had been diagnosed with early stages of SSc; study the presence of systemic involvement (at the time of diagnosis and throughout the follow-up), and the possible predictors for progression to definitive SSc. Methods: The patients were selected by consulting the clinical data from patients followed in our hospital with diagnose of early stages of SSc. Very Early SSc criteria were used to define early stage SSc. The data concerning red flags, capilaroscopy, specific auto-antibodies, systemic involvement (Gastrointestinal, Pulmonary, Cardiac, Kidney, Muscoloskeletal). Results: We obtained a sample of 70 patients, 65 being female subjects (92, 9%), with mean age of diagnosis 47, 9 years (SD 13, 6). 16 patients (22, 9%) were classified as Pre-scleroderma at the admission, 16 as Early SSc (22, 9%), 15 (21, 4%) as Very Early SSc, 16 (22, 9%) as possible SSc, 6 (8, 6%) as Limited SSc (despite not scoring to ACR criteria) and 1 (1, 4%) as Sin Scleroderma SSc. 63 patients (90%) had RP, 15 (21, 4%) had puffy fingers, 63 (90%) ANA positivity – 11 patients (15, 7%) had 1 red flag, 45 (64, 3%) had 2 red flags and 13 (18, 6%) had 3 red flags. 54 patients (78.3%) were positive to specific SSc autoantibodies; 47 patients (71.2%) had capiloroscopy compatible with SSc in different stages (17.1% Early, 12, 9% Active, 4, 3% Late and 32, 9% compatible). 54 patients (77, 1%) scored for Very Early SSc. At the moment of the diagnosis, 56 patient (81, 2%) had systemic involvement. 34 patients (48, 6%) scored to the definitive diagnosis by ACR 2013 criteria, after 2, 56 years in mean (SD 2.51) of first diagnosis. No correlation was found in what concerns to predictors of progression to SSc or systemic involvement. Conclusions: This study shed a light on the importance of the recognition of SSc's early stages, since a significant part of these patients have systemic involvement at the moment of diagnosis, yet not scoring to ACR 2013 criteria. Almost half of the patients scored to definite diagnosis of SSc at the moment of the last appointment. The importance of these findings rely on the possibility to identify systemic involvement and address it in time to prevent/delay further disease progression. References: Avouac J, Matucci-Cerinic M, Miniati I, Denton CP. Systemic Sclerosis. EULAR Online Course on Rheumatic Disease 2016 Varga J. Overview of the clinical manifestations of systemic sclerosis (scleroderma) in adults. UpToDate Jun 2016. LeRoy EC, Medsger TA Jr. Criteria for the classification of early systemic sclerosis. J Rheumatol 2001;28:1573–6.. Amato L, Gallerani I, Berti S, Fabbri P. Prescleroderma: A Distinct Stage of Systemic Sclerosis. Skinmed. 2003; 2(1). Disclosure of Interest: None declared